Odpowiedzi

2010-02-16T17:24:32+01:00
-(2x+3y)-(2x+3y)-(-3y+2x)= -2x-3y-2x-3y+3y-2x=-6x-3y
3 (a+4b-6c)-(4a+5b+4c)= 3a+12b-18c-4a-5b-4c=-a+7b-22c
3(2x-3y)-4(2x-3y)= 6x-9y-8x+12y=-2x+3y
2010-02-16T17:25:04+01:00
-(2x+3y)-(2x+3y)-(-3y+2x) =
-2x-3y-2x-3y+3y-2x =
-6x-3y


3(a+4b-6c)-(4a+5b+4c) =
3a+12b-18c-4a-5b-4c =
-a+7b-22c


3(2x-3y)-4(2x-3y) =
6x-9y-8x+12y =
-2x+3y
1 5 1
  • Użytkownik Zadane
2010-02-16T17:48:36+01:00
...
-(2x+3y)-(2x+3y)-(-3y+2x)=
-2x-3y-2x-3y+3y-2x=-6x-3y
...
3(a+4b-6c)-(4a+5b+4c)=
3a+12b-18c_4a-5b-4c=-a+7b-22c
...
3(2x-3y)-4(2x-3y)=
6x-9y-8x+12y=_2x+3y